2019
DOI: 10.31951/2658-3518-2019-a-1-155
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic analysis of viral communities in diseased Baikal sponge Lubomirskia baikalensis

Abstract: Sponges are an ecologically important component of marine and freshwater bodies. Sponge community includes a variety of microorganisms: fungi, algae, archaea, bacteria and viruses. Despite active research in the field of aquatic virology, biodiversity and the role of viruses in sponges are poorly studied. The relevance of research in this area is also related to the worldwide problem of sponge diseases. The aim of this study was to elucidate the genetic diversity of viruses in the associated community of disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…using dsRNA and ssRNA-seq also revealed a diverse RNA viral population, with matches to Totiviridae, Reoviridae and Partitivirdae [32]. Viromic studies have also provided important insights into how the viral community changes in diseased or stressed sponges [33][34][35], with thermal stress leading to an enrichment of endogenous retro-transcribing viruses in Rhopaloeides odorabile [35] and dysbiosis in the virome occurring in diseased Lubomirskia baikalensis [34]. Putative AMGs have also been detected in the viromes of some reef sponges.…”
Section: Introductionmentioning
confidence: 99%
“…using dsRNA and ssRNA-seq also revealed a diverse RNA viral population, with matches to Totiviridae, Reoviridae and Partitivirdae [32]. Viromic studies have also provided important insights into how the viral community changes in diseased or stressed sponges [33][34][35], with thermal stress leading to an enrichment of endogenous retro-transcribing viruses in Rhopaloeides odorabile [35] and dysbiosis in the virome occurring in diseased Lubomirskia baikalensis [34]. Putative AMGs have also been detected in the viromes of some reef sponges.…”
Section: Introductionmentioning
confidence: 99%
“…Myoviridae , Podoviridae and Siphoviridae ), but had considerable variability in the relative abundance of viruses targeting eukaryotic cells (such as Mimiviridae and Phycodnaviridae ). The role of viruses in host health and environmental stress responses has also been recently started to be explored and demonstrated shifts in viral community profiles ( Butina et al, 2019 ; Laffy et al, 2018 ). Furthermore evidence for genetic exchange through sponge-associated viruses has been given by the discovery of eukaryotic-like genes encoding for ankyrin proteins in bacteriophages that may provide infected bacterial hosts with an increased capacity to avoid eukaryotic phagocytosis ( Jahn et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, in Lake Baikal, recent studies have described a phage putatively infecting Polynucleobacter sp. [5], the virome associated with diseased sponges [25], and viromes from the epipelagic zone which suggested that the Baikal virome undergoes changes in composition across seasons [26].…”
Section: Introductionmentioning
confidence: 99%